Dual-arm cobot box tilting task exploration by theoretical approach - Ma, Jie Ying (Nanyang Technological University, 2023)
The use of collaborative robots, or cobots, has increased in popularity in manufacturing, especially with Industry 4.0. Dual-arm cobots have two robotic arms that work together to perform tasks with more flexibility than single-arm manipulation. However, many cobot applications still use single-arm manipulation, limiting their abilities. This constraint has motivated the exploration and development of dual-arm cobots, which can execute more complicated operations and operate in a more convenient way. One challenging task for dual-arm cobots is box tilting, which is crucial in manufacturing, particularly in the packaging and logistics industries. The optimal geometric path prediction for the dual-arm cobot to perform box tilting with maximizing the efficiency of force input is a critical research problem. In this thesis, we aim to address this challenge by developing a mathematical model using a theoretical approach to determine the optimal geometric path for box tilting. The proposed model will provide a guide for dual-arm cobot applications in manufacturing, particularly for box tilting operations, leading to more efficient and cost-effective manufacturing.